2021
DOI: 10.4103/jfmpc.jfmpc_449_21
|View full text |Cite
|
Sign up to set email alerts
|

Public awareness of early symptoms of acute myocardial infarction among Saudi population

Abstract: Introduction: Globally speaking, cardiovascular disease is the leading cause of mortality, with coronary artery disease (CAD) contributing to half of the cases. A major complication of CAD is myocardial infarction (MI). The clinical outcomes of MI are predominantly time-dependent; therefore, it is paramount that the general public is familiar with the early symptoms of MI. Aim: The main objective is to gauge the local public awareness of the early symptoms of MI, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Our study observed that 74.1% of participants had a good knowledge level, while 25.9% had a poor knowledge level. This distribution is similar to findings in other studies in America and Saudi Arabia that also identified a knowledge gap in a significant portion of the population [ 12 - 13 ]. This suggests that efforts to improve awareness should be tailored to address the needs of those with poor knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study observed that 74.1% of participants had a good knowledge level, while 25.9% had a poor knowledge level. This distribution is similar to findings in other studies in America and Saudi Arabia that also identified a knowledge gap in a significant portion of the population [ 12 - 13 ]. This suggests that efforts to improve awareness should be tailored to address the needs of those with poor knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…The current study found that 73.05% of participants had some level of knowledge about AMI. This level of awareness is consistent with global trends, where two studies in America and Saudi Arabia have reported awareness levels ranging from 60% to 80% [ 12 - 13 ]. It indicates that awareness of AMI is a concern across various regions and populations.…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, a significant percentage of participants recognized smoking, obesity, and hypertension as risk factors for MI. Our study reported that 90.3% of participants identified smoking as a risk factor, while Basham et al found that 85% of participants were aware of this association; however, the percentage difference could be attributed to the fact that the study of Basham et al had a sample size of 1,689 participants [16].…”
Section: Discussioncontrasting
confidence: 59%
“…( 31 ). Additionally, the awareness is poorer in the Saudi population ( 32 , 33 ) than in the MENA region population including Lebanon ( 34 ) and Oman ( 35 ). Spreading essential awareness among the public is warranted to minimize the incidence and mortality due to CAD in developing countries including Saudi Arabia ( 33 ).…”
Section: Discussionmentioning
confidence: 99%